The effect of noise stress on the serum testosterone level in spraque dwaley rats - Chandralekha, G.
Introduction : The noise, one.of the environmental pollutants, is considered as a strong stress factor. The environmentalists consider it as a type of pollution similar to air pollution, water pollution etc. Works were done on cardiovascular, respiratory, endocrine, and reproductive systems and on behavior. This preliminary study was designed to see the behavioral changes of the albino rats when they are exposed to noise. Objectives: To assess the effect of noise exposure (generator noise-100 decibel (dB) on the behavioral pattern of the male albino rats. Methodology: The animals were grouped as control, acute and chronic. Acute group was exposed to one hour, and three hours of generator noise exposure of IOOdB continuously/day. The chronic groups were exposed to one hour,. and 1 three hours of continuous noise exposure/day for 30 days and 45 days. The animals were keenly observed for their reaction towards the noise stress. Resu 1 t : Annoyance, disturbance, loud cry were the common features noticed when the rats were exposed to acute noise I stress of 100 dB. The rats remain confined in the cage and refused to take food'and water in chronic groups. When the ' animals were exposed to the Grip Strength test, there was significant decline in the grip of the rats belong to the acute and chronic groups. In the Splay test, the distance between fore limbs was significantly increased after exposure to noise stress 1 of IOOdB, in acute and chronic groups. The increase was time bound. 100 dB of nojse stress has significant effect on the I splay and grip strength of the rats, in acute, as well as in chronic groups.